EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH NOMOR 11 TAHUN 2012 (STUDI KASUS PENGENDALIAN KERUSAKAN HUTAN BAKAU DI KABUPATEN KEPULAUAN MERANTI) - Muslimah "; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Mangroves in Kabupaten Kepulauan Meranti have important functions as a buffer of the island from Malacca Strait waves that threatens the existence of the land coast in this regency. Therefore, the environmental sustainability must be controlled so Meranti’s land can be saved in the future. But in the fact, control of mangroves destruction has not done well. No implementation of prevention, treatment and recovery based on the contents of Regional Regulation Number 11 of 2012 . Theoretical concept used is the effectiveness by Mahmudi, who said the effectiveness have interrelationship between the output and the aim. The effectiveness focuses on outcome (result), program, or activity that are considered effective if the resulting output can meet the expected goals. The purpose of this research is to analyze the causes of non-optimal implementation of control mangroves destruction, and what can be done for implementation of Regional Regulation Number 11 of 2012 effectively. This research uses qualitative methods with descriptive data. For collecting data, researcher used interview, observation and documentation by using snowball method as the source of information data analysis trianggulasi techniques. Result of the research show that the implementation of regional regulation about control mangroves destruction had not been effective. This is caused by limited human resources, facilities and infrastructure, coordination, limited funds, and habit of society in encroachment of mangrove woods in Kabupaten Kepulauan Meranti.Keyword : Mangrove Forest, Effectiveness, Kabupaten Kepulauan Meranti